Impact of different chromium sources on physiological responses, blood biochemicals and endocrine status of heat stress in dairy calves. Issue 1 (2nd January 2022) - Keshri, Anchal; Roy, Debashis; Kumar, Vinod; Kumar, Muneendra; Kushwaha, Raju; Vaswani, Shalini; L., Vandana Kumari; Dixit, Sonam; Prakash, Atul; Choudhury, Soumen
ABSTRACT: Present experiment was conducted to examine whether the supplementation of different organic sources of Cr (Chromium) would improve the performance of heat-stressed calves. Twenty-four female Hariana calves were divided into four treatments (six calves per treatment): (1) calves fed on basal diet (0 mg Cr/kg DM); (2) calves fed on basal diet supplemented with 1.0 mg Cr/kg DM as Cr-picolinate (Cr-Pic); (3) calves fed on basal diet supplemented with 1.0 mg Cr/kg DM as Cr-polynicotinate (Cr-Polynic); and (4) calves fed on basal diet supplemented with 1.0 mg Cr/kg DM as Cr-yeast (Cr-Yeast). Supplementation of different sources of organic Cr did not alter the physiological response of heat-stressed calves during 120 days of feeding experiment. Different Cr sources did not have any effect on liver function test, protein turn over, plasma cholesterol, glucose, total immunoglobulin (Ig) and cortisol levels. Cr shows beneficial effects on cholesterol metabolism, antioxidant activity and plasma concentration of Zn and Cr. Adding Cr-Polynic in the diet of heat-stressed calves significantly reduced ( p < 0.05) plasma insulin concentration. This study suggests that the supplementation of different sources of Cr at 1.0 mg/kg DM (Dry Matter), improves antioxidant status and potency of insulin action in heat-stressed dairy calves.